Punching Glass. Issue 6 (June 2015) - Schaefer, Nathan; Cappello, Julie; O'Donohue, Peter; Phillips, Alfred; Elliott, Devlin; Daniele, Luca
<x xml:space="preserve">Abstract</x> Introduction: Punching glass can cause severe and debilitating injuries. The literature is scant in regards to the injury patterns, optimal management, and preventative strategies. We have reviewed our experience of these injuries at a regional Australian hospital. Methods: A retrospective chart review of all patients who had punched glass and presented to Cairns Base Hospital between January 2003 and December 2012. Data collected included age, gender, marital status, employment status, alcohol consumption, side of injury, intent, time of presentation, damaged structures, treatment required, operative time, total hospital stay, and required follow-up. Results: 137 eligible patients were identified during the 10-year study period. Mean age was 26.3 years. Most were men (n = 113), single (n = 122), unemployed (n = 95), and intoxicated (n = 91). Most of these injuries presented outside of normal working hours (P < 0.001). Ninety-one patients had superficial skin lacerations only and did not require operative intervention. The remaining 46 patients had a total of 46 tendon, 18 muscle, 12 nerve, 8 vessel and 5 bone injuries, and all required operative intervention. Tendon, nerve and vessel injuries were strongly associated with each other (P < 0.05). Conclusions: This represents the largest case series of glass punching injuries in the English literature. Punching glass can cause significant morbidity in a young age group and is therefore a major public health concern. Thorough physical examination, appropriate imaging and operative repair can improve outcomes. Preventative measures such as stricter legislation and safety glass will reduce the burden of these injures on the individual and healthcare system in Australia.